MENINGKATKAN KECERDASAN EMOSIONAL MELALUI METODE BERMAIN PERAN PADA ANAK USIA 5-6 TAHUN DI PAUD PERMATA HATI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - ', Sesmiwati; ', Mahdum; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Â Abstract: Based on observations of the initial studies in the field of emotional intelligence, shows that a child's emotional low. This looks uncontrolled children's emotions, irritability and often beat her. If mistakes did not apologize, do not seem to want to know about what he had done, tends to be moody and jealous of his friend. Based on the existing problems, the purpose of this study was to describe the use of role-play method can improve emotional intelligence of children aged 5-6 years in early childhood Permata Hati Benai Subdistrict Regency Kuantan Singingi. This study uses classroom action research that is designed in the form of two cycles, the cycle 1dengan 3 meetings and cycle 2 to 3 meetings. In each cycle consists of four phases: Phase Planning, Implementation Phase Action, Phase Phase Observation and Reflection. Subjects in this study were 5-6 years old children early childhood Permata Hati Benai Subdistrict Regency Kuantan Singingi totaling 12 children. The technique of collecting data through observation and documentation, while data analysis using descriptive statistics. From the data analysis, Emotional Intelligence before the cycle of children at an average of 40.41%. This suggests that emotional intelligence of children still low at under 50%. This study followed by one cycle with a yield of 46.10% with criteria began to grow and continued in cycle 2 with the result of 78.46%. Based on these results prove that there is an increase emotional intelligence of children through role-play method. This study therefore declared successful.